2014
DOI: 10.5005/jp-journals-10021-1231
|View full text |Cite
|
Sign up to set email alerts
|

Button-assisted Coronally Advanced Flap: An Innovative Ortho-perio Amalgamation

Abstract: Introduction: Esthetics has become an essential criterion of the overall treatment plan in dentistry that comprises of a healthy and beautiful smile at any age. Multidisciplinary approach involving orthodontics and periodontics results in the maintenance of a beautiful smile and a healthy periodontium. The continuous endeavor for innovation of newer interdisciplinary treatment moda lities has resulted in the use of a passive object like the orthodontic button being used to provide the initial stabilization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This procedure has also been validated as a promising technique in terms of both clinical- (root coverage, keratinized tissue height, and minimum surgical time) and patient-centered (minimum surgical time and esthetics) parameters. [ 5 6 ] Since this approach accomplishes optimum root coverage and recuperation of the original morphology of the gingival margin along with good color matching,[ 9 ] esthetically pleasing results could be achieved as seen in the current case report. Yet, the technique is not without limitations, the major limiting factor being a lack of adequate width of keratinized and attached gingiva along with the requirement for a considerable amount of vestibular space adjacent to the recession defects.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This procedure has also been validated as a promising technique in terms of both clinical- (root coverage, keratinized tissue height, and minimum surgical time) and patient-centered (minimum surgical time and esthetics) parameters. [ 5 6 ] Since this approach accomplishes optimum root coverage and recuperation of the original morphology of the gingival margin along with good color matching,[ 9 ] esthetically pleasing results could be achieved as seen in the current case report. Yet, the technique is not without limitations, the major limiting factor being a lack of adequate width of keratinized and attached gingiva along with the requirement for a considerable amount of vestibular space adjacent to the recession defects.…”
Section: Discussionmentioning
confidence: 87%
“…[ 5 ] Complete root coverage was also reported on the maxillary canine tooth at 3 months following CAF+B technique by Maroo et al . [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maroo et al in their ortho-perio amalgamation study showed postoperative results of coronally advanced flap (CAF) combination with orthodontic button to be very successful amalgamation, even in cases of Miller's Class III recession. [10]…”
Section: Introductionmentioning
confidence: 99%